“IF THERE WERE NO CLOUDS, WE SHOULDN’T ENJOY THE SUN”: THE CROSSCULTURAL VIEW AND MULTI-FACETED MEANING OF A PROVERB - Petrova, Roumyana (Proverbium - Yearbook, 2013)
This study discusses an experiment with the semantics of the English proverb “If there were no clouds, we shouldn’t enjoy the sun.” The individual interpretations of this proverb by thirty six Bulgarian bachelor students fluent in English are compared with the definition(s) of the proverb and its linguocultural semantic analysis involving the application of the cultureme. The findings reveal a large area of semantic overlap between the proverb meaning and its perception by non-English respondents.